A11 Skin fibroblasts from huntington´s disease patients show distinct signature of MIRNAS expression along disease progression. (September 2018) - Brito, Veronica; Fernandez-Santiago, Ruben; Ezquerra, Mario; Sieiro, Esther; Perez-Perez, Jesus; Kulisevsky, Jaime; Gines, Silvia
Abstract : Background: Most cellular dysfunctions in HD are associated with alterations in gene expression, with transcriptional dysregulation being a prominent feature of the disease. One of the mechanisms involved in this deregulation is the aberrant expression of microRNAs (miRNAs). Aberrant expression profiles of miRNAs have been identified as biomarkers in many different diseases. So far, several studies in the context of neurodegenerative disorders have focused on the identification and clinical application of miRNAs as biomarkers. However, the study of miRNAs in HD need to be further explored in particular related to the progression of the disease. Aims: In this study we aim to explore and validate miRNA expression profiles in fibroblasts of HD patients at pre-symptomatic and symptomatic stages. Methods/techniques: In a discovery phase we have assessed comprehensive genome-wide miRNA expression analysis of fibroblasts from pre-symptomatic, early symptomatic, middle/advanced symptomatic patients and controls. We have used the GeneChip miRNA 4.0 array from Affymetrix including probes for 2578 mature human miRNAs. In a validation phase we validated candidate miRNAs differentially expressed using the Taman Advance qPCR. Results/outcome: Our investigations have revealed specific signatures of miRNAs expression in HD patients along the disease progression with a downregulation of miRNAs at pre-symptomatic stages and an upregulation of miRNAs at symptomatic stages. Furthermore, we identified some mRNAs as biomarkers of disease progression that might identify when a patient become symptomatic such as, miR6124, miR210 and miR493, or when patients progress to a middle or advance stage of the disease, such as miR127. Conclusions: Our results indicate that miRNA alterations precede the onset of motor symptoms and highlight the potential of miRNA panels from fibroblasts as biomarkers for Huntington´s disease progression.